Paricalcitol protects against hydrogen peroxide-induced injury in endothelial cells through suppression of apoptosis - ŞEKERLER, TURGUT; ŞENER, AZİZE (My University, 2022)
The vascular endothelium is one of the main targets of oxidative stress which plays an important role in the pathophysiology of vascular damage. Recent studies show that vitamin D can positively regulate endothelial functions in various chronic diseases and in cases of increased oxidative stress. In our study, we investigated the restorative and protective potentials of paricalcitol which is frequently used in patients with chronic renal failure, a vitamin D analogue, in human umbilical vein endothelial cells (HUVEC) before and after H2O2-induced oxidative stress. Paricalcitol treatment after the oxidative stress induced by H2O2 increased cell viability in endothelial cells depending on the dose that was used. While paricalcitol (500 nM) decreased caspase-3 activity and mitochondrial membrane potential loss, it increased nitric oxide (NO) production and reduced glutathione (GSH) levels. Paricalcitol treatment before oxidative stress increased cell viability. It increased NO production and mitochondrial membrane potential while significantly reducing caspase-3 activity. While paricalcitol caused a significant inhibition of protein disulfide isomerase (PDI) reductase activity in healthy endothelial cells, it did not cause a significant change on the PDI reductase activity under oxidative stress conditions. Present study showed that paricalcitol has restorative and protective effects on endothelial cells against oxidative injury, but these effects occur at high concentrations of paricalcitol.
Keywords: Tıp; Dahili Tıp Bilimleri; Tıbbi Ekoloji ve Hidroklimatoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Medical Ecology and Hydroclimatology; Health Sciences; TIP, ARAŞTIRMA VE DENEYSEL; Klinik Tıp; Klinik Tıp (MED); MEDICINE, RESEARCH & EXPERIMENTAL; CLINICAL MEDICINE; Clinical Medicine (MED); Araştırma ve Teori; İncelemeler ve Referanslar (tıbbi); Research and Theory; Reviews and References (medical); Caspase-3; HUVEC; mitochondrial membrane potential; oxidative injury; paricalcitol; protein disulfide isomerase; VITAMIN-D; HEMODIALYSIS-PATIENTS; OXIDATIVE STRESS; NITRIC-OXIDE